2021
DOI: 10.3389/fpubh.2021.759236
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Proton Radiation and Simulated Microgravity on the Cell Viability and ALP Activity of Murine Osteoblast Cells

Abstract: Proton radiation (PR) and microgravity (μG) are two key factors that impact living things in space. This study aimed to explore the combined effects of PR and simulated μG (SμG) on bone function. Mouse embryo osteoblast precursor cells (MC3T3-E1) were irradiated with proton beams and immediately treated with SμG for 2 days using a three-dimensional clinostat. All samples were subjected to cell viability, alkaline phosphatase (ALP) activity and transcriptome assays. The results showed that cell viability decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Stable proliferation between osteoblasts and osteoclasts maintains stable bone metabolism. Osteoblast mineralization plays an essential part in osteoporosis formation of osteoporosis, and ALP activity is very important in the bone formation of osteoblasts because ALP promotes the formation of mineralization matrix proteins of osteoblasts through the hydrolysis of pyrophosphate and inorganic phosphate [ 26 , 27 ]. This study showed that there were significant differences in serum ALP levels between the OVX group and the OVX+oleuropein group.…”
Section: Discussionmentioning
confidence: 99%
“…Stable proliferation between osteoblasts and osteoclasts maintains stable bone metabolism. Osteoblast mineralization plays an essential part in osteoporosis formation of osteoporosis, and ALP activity is very important in the bone formation of osteoblasts because ALP promotes the formation of mineralization matrix proteins of osteoblasts through the hydrolysis of pyrophosphate and inorganic phosphate [ 26 , 27 ]. This study showed that there were significant differences in serum ALP levels between the OVX group and the OVX+oleuropein group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] 3D clinostat was used to explore the effects of proton radiation combined with simulated microgravity on bone function. [ 31 ] However, there are some limitations to using clinostats for the simulation of microgravity. For example, the slow‐rotating clinostat is not suitable for culturing cells or other smaller objects, while the culture volume of FRC is small, so it cannot accommodate larger samples.…”
Section: Simulated‐microgravity Bioreactorsmentioning
confidence: 99%
“…Metallic structures scatter the radiation, altering the radiation field and the dose (Kinhikar et al, 2014;Toivonen et al, 2019) at the target. To overcome this, studies have irradiated the samples first and then subjected them to simulated microgravity (Pani et al, 2016;Ma et al, 2021), but samples are not exposed to the two stressors at the same time with this protocol. Californium-252 has been used to expose samples rotating on the RPM (developed by Airbus), but dosimetry although performed was not positioned at the sample (Beck et al, 2014).…”
Section: D Clinostat Designmentioning
confidence: 99%